Theoretical Construction and Critique of Structuralist Human Geography: Development Context, Academic Contributions, and Contemporary Reflections - Liang, Chunyan (International Journal of Social Sciences and Public Administration, 2025)
Structuralist human geography emerging between the 1960s and 1980s, its theoretical foundations stem from the interdisciplinary integration of linguistics, anthropology, and Marxism, emphasizing the revelation of deep-seated social structures and power relations behind spatial phenomena from holistic and systematic perspectives. The school has propelled geography from descriptive to explanatory research, introducing core theories such as “production of space,” “capitalist spatial logic,” and “urban political economy analysis”, providing critical perspectives for understanding socio-spatial relations. However, its tendency toward structural determinism and economic reductionism limits its ability to explain individual agency and new social phenomena. Nevertheless, the theoretical legacy of structuralism remains relevant in critiques of neoliberal urbanization and environmental geography, continuously expanding its scope of application through integration with other theories. This paper explores the developmental context, academic contributions, and limitations of structuralist human geography.